Process Characterization of Ideal Porous Structure Manufacture Based on Selective Laser Melting (SLM) - Wang, Di (2016)
In order to analyze the process characterization and the design rules of porous structures, several types of porous structures were designed and produced by selective laser melting (SLM). For purpose of manufacturing a porous structure accurately, design rules based on SLM, such as the critical inclined angle of the strut, the minimum building feature and the mutual constraint among the unit cell geometrical parameters need to be considered in early stage. Other problems of the porous structure, such as powder adhesion or surface micro-pores, were analyzed. The paper also discussed another innovative design method for porous structure based on SLM technology. The obtained results provide the basis for the design of porous structure and the pre-judgment of manufacturing quality.